2019
DOI: 10.1136/bmj.l2381
|View full text |Cite
|
Sign up to set email alerts
|

Pre-eclampsia: pathophysiology and clinical implications

Abstract: Pre-eclampsia is a common disorder that particularly affects first pregnancies. The clinical presentation is highly variable but hypertension and proteinuria are usually seen. These systemic signs arise from soluble factors released from the placenta as a result of a response to stress of syncytiotrophoblast. There are two sub-types: early and late onset pre-eclampsia, with others almost certainly yet to be identified. Early onset pre-eclampsia arises owing to defective placentation, whilst late onset pre-ecla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
748
1
34

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 796 publications
(797 citation statements)
references
References 196 publications
14
748
1
34
Order By: Relevance
“…The pathophysiology of preeclampsia is complex and remains still under investigation. It is hypothesized that poor trophoblast invasion and deficient spiral artery remodeling lead to placental ischemia‐reperfusion injury 4 and the release of various angiogenic, 5 oxidative, 6 and inflammatory 7 mediators into maternal circulation, promoting generalized endothelial dysfunction, increased vascular reactivity, and activation of the coagulation cascade 8 . Risk stratification is essential in order to identify the subpopulation of pregnant women that would benefit from preventive measures early in the course of gestation, especially the administration of aspirin 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of preeclampsia is complex and remains still under investigation. It is hypothesized that poor trophoblast invasion and deficient spiral artery remodeling lead to placental ischemia‐reperfusion injury 4 and the release of various angiogenic, 5 oxidative, 6 and inflammatory 7 mediators into maternal circulation, promoting generalized endothelial dysfunction, increased vascular reactivity, and activation of the coagulation cascade 8 . Risk stratification is essential in order to identify the subpopulation of pregnant women that would benefit from preventive measures early in the course of gestation, especially the administration of aspirin 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that sFlt-1 enhances the sensitivity of endothelial cells to pro-inflammatory cytokines rather than having a pro-inflammatory effect itself. The subsequent lack of available PIGF and VEGF results in lower endogenous production of prostacyclin (PGI2) and nitric oxide (NO) and consequently leads to the vasoconstriction of placental arteries, which is crucial for the development of preeclampsia [20].…”
Section: Pathogenesis Of Preeclampsiamentioning
confidence: 99%
“…In addition to widespread endothelial dysfunction, alterations to maternal, placental and fetal metabolism are hallmarks of PE [18]. In this study, we explored third trimester placental creatine metabolism in early-onset PE and gestation-matched normotensive pregnancies.…”
Section: Discussionmentioning
confidence: 99%